Secondary education in Russia on the modern stage: state, problems, specific of management of middle general schools - N. I. Pronina; N. V. Kandaurova (Путеводитель предпринимателя, 2020)
In this article development of secondary education status is expounded in Russia, problems are analyzed, and the specific of management of middle general schools is underlined, different aspects are examined on the removal of failings in organizational-administrative activity, also thrown out suggestions of recommendation character for raising of level of management efficiency in educational establishment.